Damage tolerance of welded aluminium aircraft structures - Bussu, G. (Cranfield University, 2000)
Riveting is a traditional joining technique mostly used in the manufacturing of aircraft structures. Manufacturing studies on the next generation of wide body commercial aircraft have' indicated that the achievement of acceptable cost/benefit goals would require the» application of highly cost-effective joining processes. Although riveting provides good structural performance, it is expensive and time consuming. Welding is a candidate process t be used to manufacture large aircraft structures allowing sensible cost reductions and structural efficiency. Welded aluminium 2024-T351 structural joints produced .with a new generation of welding processes, such a Friction Stir Welding ( SW) and Plasma welding were characterised in terms of rnicrostructure, hardness and weld residual stress. Tensile properties and stress-strain behaviour of the FSW joints was investigated and discussed using simple mechanical models. The investigation of the fatigue properties of the FSW and Plasma Welded structural joints revealed the superior behaviour of the FSW joints. It was found that fatigue strength in FSW joints is dominated by surface irregularities produced by the welding process. Weld surface skimming greatly improved fatigue strength by removing surface stress concentrations. Initiation in skimmed joints occurred at locations of minimum hardness. Fatigue endurance behaviour of skimmed joints was equal or superior to that reported in riveted aluminium joints. Fatigue crack propagation studies were carried out on FSW 2024-T351 joints for cracks parallel and orthogonal to the weld direction. Crack propagation behaviour was sensitive t both weld orientation and the distance of the crack from the weld line. Growth rates both faster and slower than in the parent material were observed, depending on the crack orientation and distance from the weld. Residual stress was mechanically relieved and the effects on crack propagation observed. A comparative analysis of the results associated with crack closure measurements indicated that crack growth behaviour in the FSW joints was generally dominated by the weld residual stress. Possible design solutions for damage tolerant Welded aircraft structural components were identified and discussed in the light of the experimental results.